2023
DOI: 10.4314/ahs.v23i1.32
|View full text |Cite
|
Sign up to set email alerts
|

Association between educational attainment and risky sexual behaviour among Ghanaian female youth

Abstract: Background: Ghanaian female youth aged 15-24 years are especially vulnerable to sexually transmitted infections (STIs) compared to their male counterparts.Objectives: This study examined the association between educational attainment and risky sexual behavior among Ghanaian female youth. Method: A cross-sectional study was conducted using a nationally representative sample of youth from the 2014 Ghana Demographic and Health Survey (n=1702). The outcome of interest was risky sexual behavior, defined as ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Ethiopia, and a meta-analysis study done in developing countries [39][40][41].The other significant individual level factor of RSB was smoking status. Smokers were found to have 3.3 times higher odds of having RSB as compared to non-smokers (AOR: 3.281; 95% CI: (1.247 8.631)).…”
Section: Plos Onementioning
confidence: 99%
“…Ethiopia, and a meta-analysis study done in developing countries [39][40][41].The other significant individual level factor of RSB was smoking status. Smokers were found to have 3.3 times higher odds of having RSB as compared to non-smokers (AOR: 3.281; 95% CI: (1.247 8.631)).…”
Section: Plos Onementioning
confidence: 99%
“…Despite the social, economic, demographic, and health benefits of safe sex and consistent condom use is important in promoting women’s health and well-being, the findings of the previous studies highlighted that, the prevalence of risky sexual behavior, 17.2–24.7% in Ethiopia [ 3 , 4 ], 66.9% in Ghana [ 5 ], 28.7% in Rwanda [ 6 ], 69.5% in Bangkok [ 2 ]. The prior studies revealed that age, educational status, working status, age at first sexual intercourse, drinking alcohol, wealth index, marital status, residence, comprehensive knowledge about HIV/ADIS, tested for HIV, and ever heard about sexually transmitted infections (STI) were factors significantly associated with risky sexual behavior [ 2 4 , 6 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual reproductive health issues also feature prominently in this issue. They range from intimate partner violence 29 30 , risky sexual behavior 31 ; pathophysiology and management of pre-eclampsia 32 33 , and others. These include sexual health issues, pregnancy and its and outcome, gynecological conditions, and mental well-being 34 42 .…”
mentioning
confidence: 99%